High five, DeFi: Decentralised finance is booming. But it has yet to find its purpose. - FULWOOD, ALICE (Economist)
The article focuses on recreation of protocols on Ethereum blockchain by financial system and mentions things written into open-source code using payment system, investment funds and deposit. Topics discussed include increase in trend of decentralized finance (DeFi), risk fo counterparty defaulting elimination by locking collateral for loan and creation of dai tokens with deposition of collateral in smart contract.